Research on platform empowerment strategies for the digital transformation of SMEs from the perspective of tripartite games - Fan, Zifu; Hu, Dongyun; Wu, Leifan (Transactions on Economics, Business and Management Research, 2024)
With the current deep integration and development of the digital economy and the real economy, the industrial internet has become the key form of support for seizing the opportunities of the times and promoting the high-quality development of the real economy. The Ministry of Industry and Information Technology considers the integration of "two industries" the main line; takes the acceleration of the construction of industrial internet platforms as the starting point; and coordinates the promotion of platform system construction, benchmarking, and application promotion. Leading industries in China, as well as third-party internet companies, have successively created multiple industrial internet platforms. However, currently, most platforms offer standardized services that cannot meet the transformation needs of small and medium-sized enterprises (SMEs) at different stages. In addition, the willingness of SMEs to join these platforms is not strong, and ultimately, the desired effect has not been achieved. This article constructs an asymmetric evolutionary game model among three entities—platforms, SMEs, and the government—analyzes the evolutionary paths of the strategic evolution of each game entity and the influencing factors using the stability theorem of differential equations, and explores the evolutionary stable strategies of the system through the Jacobian matrix. Through numerical simulation, the impacts of government subsidy intensity and the platform cost-sharing ratio on the evolutionary stable strategies of the system are analyzed to explore how to promote the high-quality development of industrial internet platforms and attract a larger number of SMEs to use cloud services.